The Influence of External User Interdependence of Financial Statements, Possibility of Clients Facing Financial Difficulties, and Auditor Evaluation of Management Integrity To Acceptable Audit Risk. - Andini Sih Afsari Utami; Choirul Anwar; Susi Indriyani (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
The purpose of this research is to analyze. Analyses the influence of external users reliance on financial statements, likelihood of financial difficulties and management integrity toward acceptable audit risk were performed with 10 public accountant office who had listed from Direktorat IAPI 2013. The sample used the â€œGayâ€ theory. The analyzed method in this research uses multiple linear. The result shown that performing external users reliance on financial statements significantly influences toward acceptable audit risk, likelihood of financial difficulties significantly influences toward acceptable audit risk, and management integrity significantly influences toward acceptable audit risk. Keywords: External Users, financial Difficulties, Management Integrity, Acceptable Audit Risk